Percutaneous Reconstruction of the Stenotic Initial Segment of the Right Subclavian Artery Using the Simultaneous Kissing Stent Technique. Issue 3 (August 2015) - Zhang, Ping; Pan, Dengji; Tian, Daishi; Zhang, Qiang; Luo, Xiang
Abstract : We report a rare case of stenosis of the initial segment of the right subclavian artery treated successfully using the simultaneous kissing stent technique. A 61-year-old man with a history of systematic hypertension, hyperlipidemia, and alcohol abuse suffered recurrent and aggravated vertigo. Angiography showed severe stenosis of the initial segment of the right subclavian artery and steal from the right vertebral artery. Thus, subclavian and carotid artery stents were placed simultaneously using the simultaneous kissing stent technique. Angiography revealed excellent dilatation of the stenotic segment of the right subclavian artery and a good antegrade flow through the right vertebral artery. The steal phenomenon and the patient's vertigo disappeared, and the patency of the carotid artery (which might need further stenting) was established in advance. At his 24-month follow-up visit, the patient no longer suffered from vertigo.